Effects of GLP‐1 Receptor Agonists on Paediatric Population in a Real World Setting - A. G. Barajas; Charles A. Gagnon‐Vargas; Jessica A. Schmitt (Endocrinology, Diabetes & Metabolism)
ABSTRACT Objective Incidence of type 2 diabetes mellitus (T2DM) and obesity is increasing in children. We aimed to observe the metabolic health effects of glucagon‐like peptide 1 (GLP‐1) receptor agonists in paediatric patients with T2DM in a real‐world setting. Methods A retrospective chart review of patients aged 0 to 18 years with T2DM who were started on a GLP‐1 receptor agonist between August 2019 and August 2023 and followed for up to 24 months was included in this study. Results 321 patients were included in the analysis. After 12 months of treatment with a GLP‐1 receptor agonist, haemoglobin A1c (HbA1c) was reduced by −1.04% ± 2.3% (p < 0.001). At 24 months, HbA1c was similar to baseline (8.3% ± 2.5% vs. 7.9% ± 2.5%, p = 0.24). There was a significant (p < 0.05) decrease in the use of metformin, basal insulin, and bolus insulin at one year which was sustained at the two‐year follow‐up for metformin (p = 0.002). Overall, there was no significant change in BMI nor other metabolic parameters while undergoing treatment with a GLP‐1 receptor agonist. Conclusion Paediatric patients with T2DM using GLP‐1 receptor agonists experienced a significant decrease in HbA1c after 12 months of use, which was not sustained at 24 months. However, patients had a reduction in insulin and metformin use at 12 months. No significant impact was appreciated on BMI or other metabolic variables.